2011
DOI: 10.1194/jlr.m011825
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of adipose tissues in Zucker rats using in vivo and ex vivo magnetic resonance spectroscopy

Abstract: This article is available online at http://www.jlr.org ties ( 1-7 ), highlighting the need for effi cient means of characterizing lipid composition in vivo ( 1-7 ). Parameters such as mean unsaturation, mean polyunsaturation, and mean chain length can provide useful information about diet, fat distribution, and metabolism ( 9-14 ). The abovementioned parameters of lipid deposits can be obtained in vitro using high resolution proton magnetic resonance spectroscopy (HR-NMR) (15)(16)(17)(18)(19)(20). The disadvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…For example, in the case of corn oil the calculated amount of linoleic acid is about 17.5% less than the lowest expected value of 50.4% and the estimated amount of oleic acid is %45.7% higher than the highest expected value of 34.6%. Mosconi et al (12) determined oil and rat adipose tissue compositions using high-resolution NMR and using PRESS spectra corrected for an apparent T 2 . It was observed from their results that the obtained polyunsaturation indices from the PRESS spectra were also underestimated in both oils and rats compared with those calculated from the high-resolution spectra.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, in the case of corn oil the calculated amount of linoleic acid is about 17.5% less than the lowest expected value of 50.4% and the estimated amount of oleic acid is %45.7% higher than the highest expected value of 34.6%. Mosconi et al (12) determined oil and rat adipose tissue compositions using high-resolution NMR and using PRESS spectra corrected for an apparent T 2 . It was observed from their results that the obtained polyunsaturation indices from the PRESS spectra were also underestimated in both oils and rats compared with those calculated from the high-resolution spectra.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that there may be a link between the composition of fatty tissue and the risk of suffering from such diseases (11,12). The amounts of saturated, monounsaturated, and polyunsaturated fatty acids composing a lipid can be determined from a high-resolution NMR (nuclear magnetic resonance) spectrum of the sample.…”
mentioning
confidence: 99%
See 3 more Smart Citations